A influência do trabalho decente cooperativo na identificação organizacional cooperativa e no comportamento de cidadania organizacional - Machado, Emanuelly Comoretto (2023)
The study of decent work becomes important as the topic is one of the Goals included in the 2030 Agenda for Sustainable Development. In addition, taking into account the current global context, in which people face serious consequences in the world of work due to the situation of the COVID-19 pandemic, in particular, high unemployment and constant precariousness of work, highlight the urgent need to create and maintain quality jobs (RODRÍGUEZ, 2021). Therefore, for the promotion of decent work in organizations, cooperatives are seen as ideal, since, by their nature, they are promoting entities concerned with people, society and democratic management. With the aim of spreading this philosophy and management style, the Internacional Co-operative Alliance Strategic Plan 2020-2030 called “A People-Centered Path to a Second Cooperative Decade” was elaborated, based on the previous Plan for a Cooperative Decade, providing guidelines (INTERNACIONAL CO -OPERATIVE ALLIANCE, 2020). Among the strategies mentioned in the plan, the promotion of sustainable development objectives and cooperative identity stand out. Therefore, it is highlighted that the cooperative identity is very relevant for this study, since, from it, it is possible to establish the Co-operative Organizational Identification (IOC). Some research has already highlighted the importance of organizational identification for both employees and organizations. The more an individual identifies with their organization, the more likely they are to behave in a way that benefits the organization (MELEADY; CRISP, 2017; WILKINS; BUTT; ANNABI, 2017). Therefore, it is likely that organizational identification increases an employee's voluntary behaviors (PODSAKOFF et al., 2000). Such behaviors can be defined as organizational citizenship behaviors. Thus, based on this context, the general objective of this thesis is to analyze the influence of cooperative decent work on cooperative organizational identification and organizational citizenship behavior from the perspective of workers in educational work cooperatives in Rio Grande do Sul. For that, a descriptive, quantitative research was carried out and developed through a survey, with 123 employees of educational work cooperatives in RS. Regarding data analysis, this occurred through descriptive analysis, for the characterization of respondents, and Structural Equation Modeling was used to test the proposed investigation model. As main results of this thesis, the following stand out: the nonconfirmation of the influence of co-operative decent work on organizational citizenship behavior; co-operative decent work mediated by co-operative organizational identification influences organizational citizenship behavior; and, finally, that co-operative organizational identification influences organizational citizenship behavior.